An empirical analysis of China's dualistic economic development: 1965-2009 - Ercolani, Marco G.; Wei, Zheng (Massachusetts Institute of Technology Press, 2011)
We analyze China's rapid economic development in the context of the dualistic development theory. Over the period 1965–2009, we find that China's economic growth is mainly attributable to the development of the non-agricultural (industrial and service) sector, driven by rapid labor migration and capital accumulation. We find that the sectoral reallocation of labor plays a significant role in promoting China's economic growth. Further, we find that the marginal productivity of agricultural labor stopped stagnating in 1978, which indicates that China entered quickly into phase two of economic development with the initiation of market reforms. Moreover, by 2009, the marginal productivity of labor has likely exceeded the institutional wage, as defined by the initially low average labor productivity, indicating that China may be now in the process of entering phase three of economic development.